Capacity of the Planning Agency and National Development Plan Implementation Effectiveness: A Comparative Study of Thailand and Malaysia - Ubonloet, Patcharawan (Business Administration and Management Journal Review, 2021)
The Economic Planning Unit of Malaysia or the EPU and the Office of the National Economic and Social Development Board of Thailand or the NESDB play a major role in setting the direction of the country’s development through national development plans; namely the Malaysia Plan and the National Economic and Social Development Plan. The objectives of this study were to study the rationale for the development outcomes of Malaysia that were better than Thailand in many areas, especially after the 1997 financial crisis. The outcomes of Malaysia being better than for Thailand concerned the fact that the EPU performed its plan implementation through established planning and implementation coordination machineries that connected the Malaysia Plan and development projects that were supported by government development expenditure-led strategy. Regarding the contribution of organization theory to development plan implementation and effectiveness evaluation, the three-level capacity, namely institutional, organizational and individual capacity, can be developed as a model to investigate the planning agency capacity in order to systematically evaluate implementation effectiveness according to the performance-based approach. Building a performance delivery unit__PEMANDU—as an organization redesign strategy can close the planning, budgeting, and implementation gap.